1997
DOI: 10.1063/1.473645
|View full text |Cite
|
Sign up to set email alerts
|

Non-additive intermolecular forces from the spectroscopy of Van der Waals trimers: A comparison of Ar2–HF and Ar2–HCl, including H/D isotope effects

Abstract: Variational calculations of vibrational energies, rotational constants and angular expectation values are carried out for the trimers Ar 2 -HCl, Ar 2 -DCl, Ar 2 -HF and Ar 2 -DF. Calculations are performed on pairwise additive potential energy surfaces and on surfaces including a variety of non-additive contributions. Attention is focused on the bending levels corresponding to hindered internal rotation of the HX molecule in the complex, several of which have been observed by high-resolution spectroscopy. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
64
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 42 publications
(56 reference statements)
2
64
0
Order By: Relevance
“…Accordingly, the trimer spectra were used to develop models for the nonadditivity. 15,16 It was found that novel nonadditive terms, arising from the interaction of the HF permanent multipole moments with overlapinduced multipoles on the Ar atoms, were needed to describe the spectra.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, the trimer spectra were used to develop models for the nonadditivity. 15,16 It was found that novel nonadditive terms, arising from the interaction of the HF permanent multipole moments with overlapinduced multipoles on the Ar atoms, were needed to describe the spectra.…”
Section: Introductionmentioning
confidence: 99%
“…Electronic mail: zlatko.bacic@nyu.edu b͒ Electronic mail: j.m.hutson@durham.ac.uk tial energy surfaces, have been extended to the low-lying isomers of Ar n HF clusters with nр7 and nϭ12. 23 In a recent development, the work on nonadditive forces 15,16 and on cluster structure and dynamics 18 -22 has been brought together, and the nonadditive models developed for Ar 2 HF have been applied to larger Ar n HF clusters. 24 The nonadditive potentials were found to account remarkably well for the frequency shifts for nϭ3 and n ϭ4, 24 which were the largest Ar n HF clusters that had then been observed.…”
Section: Introductionmentioning
confidence: 99%
“…Investigations of the nonadditive forces in the Ar 2 HF complex using ab initio electronic structure calculations have included the applications of supermolecular Møller-Plesset perturbation theory by Szczȩśniak, Chała-sinski, and co-workers 10,11 and symmetry-adapted perturbation theory by Moszynski and co-workers. 16 Hutson and co-workers 2,12,14,[21][22][23] have developed and tested a model of the nonadditive forces in Ar 2 HX ͑where X ϭ halogen͒ including dispersion, induction, exchange overlap and exchange multipole interactions. Ernesti and Hutson 14 found that their total-1 model ͑referred to hereafter as the EH potential͒ reproduced well the vibrational band origins and frequency shifts for Ar 2 HF, Ar 2 DF, Ar 2 HCl, and Ar 2 DCl in the H/DX vϭ0 and 1 states.…”
Section: Introductionmentioning
confidence: 99%
“…16 Hutson and co-workers 2,12,14,[21][22][23] have developed and tested a model of the nonadditive forces in Ar 2 HX ͑where X ϭ halogen͒ including dispersion, induction, exchange overlap and exchange multipole interactions. Ernesti and Hutson 14 found that their total-1 model ͑referred to hereafter as the EH potential͒ reproduced well the vibrational band origins and frequency shifts for Ar 2 HF, Ar 2 DF, Ar 2 HCl, and Ar 2 DCl in the H/DX vϭ0 and 1 states. The model has also been extended to Ar n HF clusters 24 and shown to reproduce the observed vibrational shifts for nϭ3 and 4.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation